Experimental studies for thin layer model validation and microwave drying characteristics of beetroot considering energy optimization. (15th August 2023) - Ahmed, Mukhtar; Faisal, Mohd; Laskar, Abdullah; Abdullah, Anas; Shahadat, Mohammad; Umar, Khalid; Kamyab, Hesam; Ubaidullah, Mohd; Pandit, Bidhan; Prakash, Chander; Yusuf, Mohammad
Graphical abstract: Abstract: The drying kinetics of Beetroot was studied experimentally, followed by mathematical modeling. This work reveals the effect of input electrical power at 300, 600, and 800 W on the drying kinetics of Beetroot. The thin layer drying behavior of beetroot specimens was studied by employing seven distinct mathematical models. The models studied were contrasted between experimental and simulated moisture ratios based on their correlation coefficient and root mean square error values. The results indicate the page model as the best-suited model with values of correlation coefficient from 0.9881 to 0.9944 and root mean square error values from 0.0213 to 0.043 to define the thin layer beetroot drying behavior. The drying time was significantly reduced by about 400 s by raising the microwave output power by 500 W, i.e., from 300 W to 800 W. The drying process was noted to occur mainly during the falling rate period. The average moisture diffusivity varied between 1.78 × 10 −8 and 4.38 × 10 −7 m 2 /sec, whereas the values of activation energies determined were 69.99, 90.87, and 50.82 W/g for the cube, slab, and disc samples, respectively. The energy consumption and specific energies decreased with an increase in microwave power during drying. It was estimated that their values were in the range of 108–324 kJ and 16.57–49.54 MJ/kg water, respectively. Further, moisture diffusivities decreased with decreasing microwave power.